(untitled) (Revista ESASP - Revista Científica Virtual da Escola Superior de Advocacia da OAB/SP, 2025)
The article analyzes the introduction of the Incident of Disregard of Legal Personality (IDPJ) in labor proceedings by Law No. 13,467/2017. The author argues that importing this institute from the CPC/2015 ignores the specialty and speed of the labor rite, potentially acting as a procrastinating mechanism in the execution phase. Practical reflections, recursive nuances, and the need for measures such as urgent relief to mitigate the delay in the satisfaction of alimony credits are discussed. (Received: July 2025 | Accepted: September 2025).